Barriers to the accessibility of health insurance in elderly patients attending NCD clinic in a tertiary care hospital Trichy, Tamil Nadu: a mixed-method study - Suryawanshi, Deodatt M.; Rajasehran, Divya; Gunasekaran, Kalaipriya; Anzbhagan, Suguna; Mali, Sandeep (International Journal Of Community Medicine And Public Health, 2024)
Background: Health insurance schemes launched by governments have been inadequate to provide health coverage to the vulnerable elderly population. This research aimed to study the prevalence, preference, and pattern of health insurance coverage among the study participants and barriers to its accessibility. Methods: It was a facility-based Sequential explanatory mixed-method study where patients above 60yrs attending the non-communicable disease OPD were recruited by systematic random sampling and enquired using a semi-structured questionnaire for the prevalence, preference, and pattern of health insurance. Focussed Group discussions (FGD) were later conducted to explore the barriers faced by participants in accessing health insurance. Results: Health Insurance coverage among the study participants was 74.5%. Of the participants who had any type of health insurance, 86.7% had public health insurance. About three fourth (73.8%) of those who had health insurance were covered under the CMCHIS. Mean health insurance coverage provided was significantly higher by private health insurance (INR170897.4) as compared to both the LIC and CMCHIS (p<0.01) while premium charged was significantly higher for LIC (INR 10003.3/yr.) as compared to others (p<0.01). Institutional issues, lack of awareness, and economic dependence on children were considered as barriers to the accessibility of health insurance among elderly. Conclusions: A dedicated universal Health Insurance Programme with higher monetary coverage and low premium involving all elderly populations may provide necessary financial risk protection and reduce out-of-pocket health expenditure.